Survival of Listeria innocua on Fuji apples under commercial cold storage with or without low dose continuous ozone gaseous. (December 2018) - Sheng, Lina; Hanrahan, Ines; Sun, Xiaofei; Taylor, Michael H.; Mendoza, Manoella; Zhu, Mei-Jun
Abstract: This study evaluated the fate of Listeria innocua, a non-pathogenic species closely related to Listeria monocytogenes, on Fuji apple fruit surfaces during commercial cold storage with and without continuous low doses of gaseous ozone. Unwaxed Fuji apples of commercially acceptable maturity were inoculated with 6.0–7.0 Log10  CFU L. innocua/ apple, and subjected to refrigerated air (RA, 33 °F), controlled atmosphere (CA, 33 °F, 2% O2, 1% CO2 ), or CA with low doses of ozone gas (50.0 –87.0 ppb ) storage in a commercial facility for 30 weeks. A set of uninoculated apples was simultaneously subjected to the above storage conditions for total plate count and yeasts and molds enumeration. L. innocua survival under RA and CA storage was similar, which led to 2.5–3.0 Log10  CFU/apple reduction during storage. Continuous gaseous ozone application decreased L. innocua population on Fuji apples to ∼1.0 Log10  CFU/apple after 30-week storage, and suppressed apple native flora. CA storage delayed apple fruit ripening through reduction of apple firmness and titratable acidity loss, and low dose gaseous ozone application had no negative influence on apple visual quality, including both external and internal disorders. In summary, L. innocua decreased on Fuji apple surfaces during commercial long-term RA and CA storage. Ozone gas has the potential to be used as a supplemental intervention method to control Listeria spp. and to ensure fresh apple safety. Highlights: Commercial cold storages (RA and CA) decreased L. innocua on Fuji apples by ∼2.5 Log10  CFU/apple during 18 weeks. RA caused ∼1.0 Log10  CFU/apple more reduction than CA during 30-week storage. Continuous low doses of gaseous ozone application in CA reduced L. innocua by ∼5.0 Log10  CFU/apple during 30-week storage. Continuous low-dose gaseous ozone application inhibited apple background flora without negative impact on fruit quality.